Funcionalidade e estado geral de saúde em idosos com dor lombar agudizada: um estudo longitudinal - Juliana Pantuza Vilar Ribeiro (2014)
There is an increase in life expectancy and in the proportion of elderly in brazilian population. The majority of this population have chronic diseases and disabilities. Among the possible elderly health problems there is low back pain (LBP) which is a common condition in the population it impacts on functional performance and the manner in which the individual realize his own health. The aim of this study was to evaluate the association between low back pain intensity (PI), functional performance (FP) and the perception of general health (PGH) in elderly and the change in these responses after six months. Its an observational longitudinal study conducted with a subsample of the epidemiological study Back Complaints in the Elders BACE. In 188 elderly patients with LBP, the PI was evaluated by the Numerical Pain Rating Scale, the FP by the Late-Life Function and Disability Instrument and the PGH by the Short-Form Health Survey. The data were subjected to statistical analysis: descriptive, Paired t Test to test the hypothesis of mean difference in pain over time, the McNemar Test to verify the change in the frequencies of the elderly according to the levels of PI and PGH, Wilcoxon Test to test the changes in scores for frequency and limitation, Kruskal-Wallis and Mann-Whitney Tests to compare the scores of instruments between variables, finally, the association between the PI and the PGH was evaluated by Chi -square with linear trend. There was a predominance of women in the study sample (89,4%), and their mean age was 68.4 years. The results of this study indicate that there was a decrease in mean of PI and in the percentage of individuals with severe pain after six months, however 52.2% of the sample remained with the same ID, 40.4% with severe low back pain. FP and the PGH had no statistically significant change. The pain was associated inversely with FP, ie, worst FP was found in elderly patients with severe pain. A positive perception of health was associated with a mild pain. The FP showed a direct relationship with PGH, ie worst FP was associated with poorer health perception. From the results of this study it was possible to know the profile of elderly patients with acute exacerbation episode of low back pain. It was found that after six months, the frequency of elderly patients with severe pain reduced, while the functional performance and the perception of general health remained. Furthermore, the intensity of pain is inversely related to the perception of general health status and functional performance, which was only observed after six months. Finally, the perception of general health and functional performance maintained direct relationship.